2016
DOI: 10.1021/acs.langmuir.6b03009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oil Exchange in Nanoemulsions Prepared with the Phase Inversion Concentration Method

Abstract: Nanoemulsions (NEs) are metastable emulsions with droplet sizes between 20 and 100 nm and with a wide range of applications, for example, in polymerization, in pharmaceutical and cosmetic formulations, and as drug delivery systems. Even though they are not in thermodynamic equilibrium, they can be metastable over relatively long times and have the advantage that they can be formed easily by low energy input methods. In particular, the phase inversion concentration (PIC) method allows the formation of NEs by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Hoffmann et al interpret small angle neutron scattering data on the exchange in nanoemulsions and conclude that only Ostwald ripening is the main mechanism for exchange. 42 They attribute the main factor for diffusion to the solubility of the dispersed alkene in water, hardly influenced by the choice of a specific surfactant. The observation of reduced Ostwald ripening with longer alkenes is in line with Kabalnov 32 and confirms theoretical expectations.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Hoffmann et al interpret small angle neutron scattering data on the exchange in nanoemulsions and conclude that only Ostwald ripening is the main mechanism for exchange. 42 They attribute the main factor for diffusion to the solubility of the dispersed alkene in water, hardly influenced by the choice of a specific surfactant. The observation of reduced Ostwald ripening with longer alkenes is in line with Kabalnov 32 and confirms theoretical expectations.…”
Section: ■ Discussionmentioning
confidence: 99%
“…11,12 Despite the fact that both systems have oil, water and surfactant as their constituents as well as little variations in the physicochemical attributes, the distinction prevails in terms of surfactant concentration, and thermodynamic and kinetic stabilities. [12][13][14][15][16] One of the most formidable challenges in the formation of nanoemulsions is the attainment of 1 : 1 oil-surfactant stoichiometries, where co-surfactants or additive sources can play a crucial role. Despite such immense potential to facilitate an improved structural expression of the dispersed phase, the formation of long-term stable food grade nanoemulsions has emerged as a daunting task for food chemists.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In nanoemulsions stabilized by polyglycerol-4 laurate or disodium laureth sulfosuccinate, oil exchange took place via diffusion of the oil molecules through the aqueous phase, and it was concluded that coalescence played hardly any role in these systems. 19 Droplet adhesion decays with the droplet diameter, so small droplet size prevents nanoemulsions from undergoing flocculation. 20 As it is theoretically substantiated, 21 the enhanced stability of nanoemulsions towards flocculation is attributed to the high value of d/r, where d is the thickness of the adsorbed layer and r is the droplet radius.…”
Section: Introductionmentioning
confidence: 99%